Scaly-sided Merganser (Mergus squamatus) equalizes foraging costs with depth by switching foraging tactics - Peizhong Liu; Meihan Liu; Dongyang Xiao; Ying He; Rong Fan; Cai Lu; Li Wen; Qing Zeng; Guangchun Lei (Avian Research, 2023)
Throughout evolutionary history, animals are finely tuned to adjust their behaviors corresponding to environmental variations. Behavioral flexibility represents an important component of a species' adaptive capacity in the face of rapid anthropogenetic environmental change, and knowledge of animal behaviors is increasingly recognized in conservation biology. In aquatic ecosystem, variation of water depth is a key factor affecting the availability of food; thus, the foraging behaviors of many waterbirds, especially piscivores. In this study, we compared the foraging behaviors of the Scaly-sided Merganser (Mergus squamatus), an endangered migratory diving duck endemic to East Asia, in habitats with different water depths (Shallow waters: 0–40 ​cm; Deep waters: 40–300 ​cm), using video camera records obtained from the known wintering sites during three winters from 2018 to 2020. Further, the energy expenditure of foraging behavior profile and energy intake based on fish sizes were calculated to study the foraging energetics. In total, 200 effective video footages that contained 1086 ​min with 17,995 behaviors and 163 events of catching fish were recorded. Results showed that: 1) time length for fishing (including eye-submerging, head-dipping, diving and food handling) of M. squamatus in shallow waters was significantly more than in deep waters; 2) M. squamatuss spent significantly more time for preparing (including vigilance, preening and swimming) in deep waters than in shallow waters; 3) the mean catch rate was 0.28 fish/min in shallow waters, which is significantly higher than the value of 0.13 fish/min in deep waters; 4) despite the distinct foraging behavior profiles and energy intakes, M. squamatus showed similar energetics in shallow and deep waters. We concluded that M. squamatus is a good example of behavioral flexibility that aligns with expectations of optimal foraging theory, in that it behaves in accordance to resource availability in different environments, resulting in high foraging efficiency.